Dispossession, violence, resistance: First Nations and Mapuche women in the face of settler colonial patriarchy - Nunez, Piaroa (2025)
Land dispossession by European colonizers in what we know as North, Central, and South America brought about the erasure of Indigenous cultures, traditions, and languages across the region, including First Nations in Canada and the Mapuche people in Chile, whose resistance against settler colonialism continues to resonate today. This paper presents a comparative analysis of First Nations and Mapuche women's experiences within colonial patriarchy, using an interdisciplinary approach by integrating a review and analysis of historical, feminist, and decolonizing secondary sources. Using settler colonialism as a framework, the first section reviews the European processes of colonization and the settler-Indigenous relations to the land and property rights in what is now Canada and Chile, comparing the colonial methods of land dispossession and unveiling how the attempts to control First Nations and Mapuche people through their lands were part of these settler-colonial projects. The second section uses patriarchal colonialism and cuerpo-territorio to understand how colonial assimilation policies and systemic marginalization relate to direct forms of violence against Indigenous women. From the structural issues behind missing and murdered Indigenous women and girls (MMIWG) in Canada to militarized violence against Mapuche communities in Chile, it explores the continuous impact of colonial policies on Indigenous women. Finally, based on research on First Nations women's activism and Mapuche women's efforts within and beyond their communities, the last section will examine how Indigenous women have organized and challenged colonial patriarchy. This section will provide insight into how Indigenous women have fought against oppressive systems historically and what this means for decolonizing the present and future. May 2025